2014
DOI: 10.1016/j.ygyno.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Does risk of endometrial cancer for women without a germline mutation in a DNA mismatch repair gene depend on family history of endometrial cancer or colorectal cancer?

Abstract: Objective To determine whether risk of endometrial cancer for women without a germline mutation in a DNA mismatch repair (MMR) gene depends on family history of endometrial or colorectal cancer. Methods We retrospectively followed a cohort of 79,166 women who were recruited to the Colon Cancer Family Registry, after exclusion of women who were relatives of a carrier of a MMR gene mutation. The Kaplan-Meier failure method was used to estimate the cumulative risk of endometrial cancer. Cox regression was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 34 publications
3
23
0
1
Order By: Relevance
“…57). This risk is increased further if 2 or more first-or second-degree relatives have previously had endometrial cancer (HR, 8.73; 95% CI, 4.25-17.9; P < 0.001).…”
Section: Genetic Risk Scorementioning
confidence: 99%
“…57). This risk is increased further if 2 or more first-or second-degree relatives have previously had endometrial cancer (HR, 8.73; 95% CI, 4.25-17.9; P < 0.001).…”
Section: Genetic Risk Scorementioning
confidence: 99%
“…Colon cancer carcinogenesis has been reported to be associated with genetic errors in genes involved in apoptosis and cell proliferation (Davies et al, 2005;Watson, 2006;Damaschke et al, 2013;Bharati et al, 2014). Genetic defects triggering aberrant activation of Wnt/ -catenin signalling are common and are reported in over 90% of sporadic cases of colon cancer (Miyaki et al, 1994;Clevers, 2006;Klaus and Birchmeier, 2008;Schon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3 Several studies have reported an increased risk of endometrial cancer for women with at least one firstdegree relative (mother, sisters, or daughters) affected with endometrial cancer; however, risk estimates have been inconsistent. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Furthermore, some studies have estimated associations of risk of endometrial cancer with familial clustering of cancers of the colon, rectum, breast, ovary, and cervix, and these estimates have also been inconsistent. [4][5][6][7][8][9][10][12][13][14][15]17,23,24 Despite the attention directed toward the potential role of family history in endometrial cancer risk, quantification of relative risk (RR) of cancer specific to site in first-degree relatives has not been adequately determined.…”
Section: Tabulation Integration and Resultsmentioning
confidence: 99%
“…Of the 10 case-control studies, four used hospital attendees without any cancer diagnosis as control participants. 4,8,12,13 Five studies estimated risk of endometrial cancer associated with a family history of cancer up to seconddegree relatives 9,13,14,17,23 and one study estimated risk up to third-degree relatives. 16 Of the 14 studies that reported an association between a family history of endometrial cancer and risk of endometrial cancer, 4-17 nine reported clear evidence for an increased risk of endometrial cancer for women with at least one first-degree relative with endometrial cancer compared with those without a family history.…”
Section: Resultsmentioning
confidence: 99%